Using life cycle assessment in environmental engineering education. Issue 1 (1st January 2019) - Burnley, Stephen; Wagland, Stuart; Longhurst, Phil
ABSTRACT: Life cycle assessment (LCA) is a method of assessing the environmental impacts of the manufacture and use of a product or provision of a service such as waste management. LCAs are based on quantitative science, but softer skills are also required in interpreting the results. Therefore, LCA provides an ideal opportunity for students to develop and apply both quantitative and qualitative skills in order to address complex real-world problems. In this research a simplified spreadsheet LCA tool was produced for students to assess the environmental impacts of a waste management system. Detailed feedback from face to face and distance-learning students were positive about the tool, with students welcoming the detail provided in the results and the use of a practical example to help their learning. In conclusion, LCA is an effective way of encouraging environmental and engineering students to develop and apply a wide range of transferable skills.